Effectiveness of Task-Oriented Physiotherapy in Improving Balance and Gait in Post-Stroke Patients (Journal of Advances and Scholarly Researches in Allied Education, 2026)
One of the primary causes of long-term disability is stroke, which often results in issues with gait and balance. Task-oriented physiotherapy, which emphasizes functional, goal-directed activities, is one potential method of rehabilitation. How much may task-oriented physical therapy aid stroke victims in regaining their walk and balance? That was this study's main objective. A narrative review was conducted using electronic databases, including PubMed, Scopus, CINAHL, EMBASE, and Google Scholar, and included studies published in English between May and June 2025. Keywords included "stroke," "post-stroke," "task-oriented physiotherapy," "balance," "gait," and "rehabilitation." Research involving persons who had experienced a stroke, were receiving task-oriented physical therapy, and had outcomes related to their gait or balance qualified for inclusion. We succeeded in including seventeen studies. The study's design, participant characteristics, treatments, outcome measures, and results were all reported narratively. Throughout all 17 trials, task-oriented physiotherapy continuously improved functional outcomes. Using the TUG test, there was an improvement in gait speed in eight trials, walking endurance in nine, balance in nine, and functional mobility in ten. High-intensity, progressive, and functionally relevant task-oriented exercises had greater outcomes than standard therapy. The majority of studies had moderate to outstanding research quality. Task-oriented physical therapy may help stroke survivors improve their functional mobility, gait, and balance. The therapeutic benefits are improved when traditional stroke rehabilitation programs include task specificity, repetition, and increasing complexity.